Caught between Scylla and Charybdis? Regulating Bank Leverage When There Is Rent Seeking and Risk Shifting - Acharya, Viral V.; Mehran, Hamid; Thakor, Anjan V. (The Review of Corporate Finance Studies, 2015)
We develop a theory of optimal bank leverage in which the benefit of debt in inducing loan monitoring is balanced against the benefit of equity in attenuating risk shifting. However, faced with socially costly correlated bank failures, regulators bail out creditors. Anticipation of this generates multiple equilibria, including one with systemic risk in which banks use excessive leverage to fund correlated, inefficiently risky loans. Limiting leverage and resolving both moral hazards—insufficient loan monitoring and asset substitution—requires a novel two-tiered capital requirement, including a “special capital account” that is unavailable to creditors upon failure. Received April 23, 2015; accepted September 16, 2015 by Editor Paolo Fulghieri.